Effect of Gamma-Irradiated Recycled Low-Density Polyethylene on the High- and Low-Temperature Properties of Bitumen - Perviz Ahmedzade; Alexander Fainleib; Taylan Günay; Olga Starostenko; Tetyana Kovalinska (International Journal of Polymer Science)
This paper describes polymer modification of bitumen with gamma-irradiated recycled (γ-LDPER) low-density polyethylene. The recycled low-density polyethylene (LDPER) was obtained from greenhouse films exposed to sunlight at least one year. The surface of the LDPER was treated by gamma beam irradiation that provided formation of free radicals and some functional groups that may contribute to the creation of strong chemical bonds between polymer modifier and bitumen. Five different samples of bitumen/γ-LDPER compositions with the modifier content, wt. %: 1, 3, 5, 7 and 9, were prepared. The effects of the γ-LDPER on original and aged bitumen were investigated by means of morphological, chemical, and physical testing program, including FTIR spectroscopy, conventional tests, rotational viscosity (RV), dynamic shear rheometer (DSR), and bending beam rheometer (BBR) tests. Superior performing asphalt pavements (Superpave) specifications were used to analyze mechanical test results as well as to determine the performance grades (PG) of the binders. Optimum usage of the γ-LDPER as modifier in bitumen were suggested after testing program. The results reveal the stiffening effect of the γ-LDPER on bitumen that provide enhanced temperature susceptibility and also promise better performance grades (PG) with γ-LDPER polymer modification.